Devonian agglutinated polychaete tubes: all in all it's just another grain in the wall. Issue 1955 (28th July 2021) - Becker-Kerber, Bruno; Horodyski, Rodrigo Scalise; del Mouro, Lucas; Sedorko, Daniel; Lehn, Ilana; Sanchez, Dario Ferreira; Fournier, Jérôme; Mazurier, Arnaud; El Albani, Abderrazak
Abstract : Biomineralized and organic metazoan tubular skeletons are by far the most common in the fossil record. However, several groups of organisms are also able to agglutinate particles to construct more rigid structures. Here we present a novel type of agglutinated tube from the austral and endemic palaeobiota of the Malvinokaffric realm (Devonian, Brazil). This fossil is characterized by an agglutinated tube made of silt-sized particles forming an unusual flanged morphology that is not known from the fossil record. Besides being able to select specific particles, these organisms probably lived partially buried and were detritus/suspension feeders. Comparisons across different modern groups show that these fossils are strongly similar to tubes made by polychaetes, specifically from the family Maldanidae. If this interpretation is correct, then an early divergence of the Sedentaria clade may have occurred before the Devonian.